CT of Anatomic Variants of Sinonasal region and its correlation with symptoms of Rhinosinusitis - Muhammad Saleem Akhter, Javaria Akhtar, Shahid Ali, Hassan Raza Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Sinonasal region is subjected to wide anatomical variation. The paranasal sinuses (PNS) create a connection with nasal cavity. They are placed in close proximity to nose. The four paranasalsinuses ;maxillary, ethmoid, sphenoid, and frontal, are named after their coinciding bone. Computed Tomography (CT Scan )is important modality to describe the location of these paranasal sinuses. Aim: To ascertain the frequency of various anatomic variants of sinonasal region in population of Sahiwaland itsassociation with symptoms of rhinosinusitis. Methods: This descriptive cross sectional study was conducted in Sahiwal Teaching Hospital from 10th June 2022 – 10th December 2022, with collaboration of Radiology and otorhinolaryngeology Departments. 60 symptomatic subjects between 18-60 years of age, irrespective of gender with rhinosinusitiswere taken.They underwent CT Scan of paranasal sinuses. The findings of CT Scan related to nasal-septum, turbinates, uncinate process, ethmoid air-cells and other anatomical variants corresponded with symptoms of rhinosinusitis. The data was analyzed using SPSS version 23.0. Frequency, percentages and p-value of different variants were calculated. The p-value of ≤ 0.05 was considered as significant. Results: Our study showed 63.3% males and 36.7% females. The mean age of our subjects was 30.65 + 12.7 years. The most frequently seen anatomical variants in our population were nasal septum deviation (86.7%) followed by aggernasi cells (68.3%) and asymmetry of both sides of sphenoid sinuses (68.3%). The statically significant association was noted between concha bullosa of middle turbinate and nasal obstruction ( p-value 0.001) and between rhinorrhea and asymmetry of both sides of sphenoid sinus ( p-value 0.035) Practical Implications & Conclusion: We concluded from our study that that however there is no significant association between rhinosinusitis and most of the anatomic variants of sinonasal region except concha bullosa of middle turbinate and asymmetry of both sides of sphenoid sinus. But to avoid operative complexities, a surgeon must be well aware of these diverse variants. Keywords: Anatomical variations, CT-scan, Rhinosinusitis